1999
DOI: 10.1021/jo990594s
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Isoquinolines by Noyori Transfer Hydrogenation:  Enantioselective Synthesis of Chiral Diamines Containing an Aniline Subunit

Abstract: Transfer hydrogenation using the Noyori catalyst 5-Ts is effective for the enantioselective hydrogenation of imines containing fully substituted nitrogen groups (12 or 13). Analogues such as 11c could not be reduced in practical yield, apparently due to product inhibition of the catalyst. Asymmetric transfer hydrogenation of the aniline imine 8a was possible, but required impractical purity levels for the substrate, and the nitro analogue 7 could not be reduced efficiently. The best results were obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 9 publications
0
59
0
Order By: Relevance
“…In some early examples, Vedejs et al used a Noyori catalyst to synthesize new asymmetric proton donors [188] and Sheldon and coworkers produced a key intermediate in the synthesis of morphine [189]. A group of researchers at Glaxo Wellcome published the syntheses of the neuromuscular blocker GW0430 and related compounds using transfer hydrogenation as a key step [190,191].…”
Section: Syntheses Using the Asymmetric Transfer Hydrogenation Of Imimentioning
confidence: 99%
“…In some early examples, Vedejs et al used a Noyori catalyst to synthesize new asymmetric proton donors [188] and Sheldon and coworkers produced a key intermediate in the synthesis of morphine [189]. A group of researchers at Glaxo Wellcome published the syntheses of the neuromuscular blocker GW0430 and related compounds using transfer hydrogenation as a key step [190,191].…”
Section: Syntheses Using the Asymmetric Transfer Hydrogenation Of Imimentioning
confidence: 99%
“…In some early work, Vedejs was able to obtain some excellent results through reaction optimization but also found that the reaction was highly dependent on the structure of the substrate (Scheme 11.12 ) [43] . The desired product of Vedejs ' study was the ortho -amino -substituted (20) , for use as a chiral hydrogen donor.…”
Section: Tetrahydroisoquinolines and Tetrahydro -B -Carbolinesmentioning
confidence: 99%
“…Transfer hydrogenation using stable organic hydrogen donors such as 2-propanol or formic acid is an attractive solution to the above demand. Some recent examples include tetrahydroisoquinolines (13) [47,48] and indole alkaloids (14)(15)(16) [49]. The methodology has been applied to a numerous synthesis of optically active amines.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%